A novel copper-rich open-framework chalcogenide constructed from octahedral Cu4Se6 and icosahedral Cu8Se13 nanoclusters. Issue 22 (9th February 2016) - Yang, Huajun; Wang, Le; Hu, Dandan; Lin, Jian; Luo, Li; Wang, Hongxiang; Wu, Tao
Abstract : A unique open-framework chalcogenide was constructed from two kinds of cluster-based secondary building units (SBUs), namely, the icosahedral Cu8 Se13 cluster and the octahedral Cu4 Se6 cluster. Abstract : We demonstrated a unique copper-rich open-framework chalcogenide constructed from icosahedral Cu8 Se13 and octahedral Cu4 Se6 nanoclusters connected to each other through a SnSe3 (Se2 ) bridging unit. The specific copper-rich composition gives rise to a narrow band gap and photoelectrical responsive properties in the infrared range.